Contribution of cloud computing in the reduction of carbon dioxide emission - Khan, Nusratullah; Nusatullah, Kajal; Shah, Asadullah (International Educative Research Foundation and Publisher (IERFP), 2014)
The Information Technology industry is rapidly expanding and as a result its contribution to carbon dioxide emission is also rapidly increasing. Fortunately, the cloud computing industry is perceived by many to be a viable solution for reducing carbon dioxide emissions. Accordingly, there are numerous studies which try to prove that cloud computing can reduce carbon dioxide emissions up to more than half of the current carbon dioxide emissions. In this paper, two of such studies where reviewed to assess whether cloud computing is indeed a viable candidate for limiting and reducing the amount of carbon dioxide emitted by the IT industry. All the information gathered in this paper prove that; cloud computing is a promising technology which could reduce carbon dioxide emissions. The percentage of decrease can range from 10% to 90%. The effectiveness of the carbon dioxide emission reduction process is highly dependent on the size of the business organization. Accordingly the size of the organization is negatively correlated to the efficiency of carbon dioxide reduction. This means that as the size of the organization increase, carbon dioxide emission reduction decrease. This paper also presented the four reasons why cloud computing can reduce carbon dioxide emissions, which are: dynamic provisioning, multi-tenancy, server utilization, and data center efficiency.